Implikasi Pemutusan Hubungan Kerja Sepihak Bagi Hak Pekerja Pasca UU Cipta Kerja - Tanera, Lauren; Gunadi, Ariawan (Legal Standing : Jurnal Ilmu Hukum, 2025)
Unilateral termination of employment is a labor issue that has the potential to cause significant economic and welfare impacts on workers. The act of terminating employment without a clear legal basis and without fulfilling workers' rights contradicts the principle of fairness in the industrial sector. This study aims to examine the legal protection aspects for workers who experience termination without mutual agreement and to analyze the role of the government in addressing this issue. This research employs a normative approach by analyzing applicable legal provisions, including legislation and court decisions. Based on Article 28D (2) of the 1945 Constitution of the Republic of Indonesia and Article 81, point 47 of the Omnibus Law, which revises Article 156(1) of the Manpower Law, workers who experience termination of employment are entitled to compensation in the form of severance pay, long-service appreciation pay, and compensation for other entitlements. Additionally, the government plays a key role as a policymaker and mediator in labor dispute resolution. Although regulations provide a legal foundation for protecting workers' rights, cases of unfair termination continue to occur due to weak enforcement and limited worker awareness of their rights. Therefore, concrete measures are necessary to strengthen law enforcement, enhance oversight of labor regulation implementation, and optimize the government's role in ensuring the protection of workers' rights.